Freshwater budget in the Persian (Arabian) Gulf and exchanges at the Strait of Hormuz - Campos, Edmo (2020)
This paper has two related data sets: (1) Campos, E. (2020). GULF HYCOM 1/12 Data Set for Paper PONE-D-20-06928R1. DANS. https://doi.org/10.17026/dans-xhy-3ap3 ; (2) Campus, E. (2020). Output from a 1/12-degree Global experiment with the Hybrid Coordinate Ocean Model (HYCOM), forced with with NCEP Reanalysis products - Data for the Persian Gulf and Strait of Hormuz. SEANOE. https://doi.org/10.17882/74042 This work is funded by the American University of Sharjah Faculty Research Grant (FRG) program (Grants FRG19-M-G67 to EJDC and FRG19-M-G74 to GC). The analyses used results of numerical experiments run at the Brazilian National Institute for Space Research (INPE) Tupã supercomputer and at the Laboratory for Ocean Modeling and Observations (LABMON), of the Oceanographic Institute of the University of São Paulo, Brazil, as part of Projects SAMOC-BR and SAMBAR, sponsored by the São Paulo State Foundation for Research Support (grants 2011/50552-4 and 2017/09659-6) to EJDC. EJDC acknowledges the Brazilian Council for Scientific and Technological Development (CNPq) for a Research Fellowship (Grant 302018/2014-0).